THE DIFFERENCE LEVEL OF MYELOPEROXIDASE IN PLATELET CONCENTRATE BASED ON PREPARATION METHOD AND STORAGE DURATION - Fuad Anshori; Teguh Triyono; Tri Ratnaningsih (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
The thrombocyte concentrate (TC) preparation process through its storage affects the platelets contained inside. The contaminating leukocytes in TC is an important factor implicated in storage lesion on TC during storage. Leukodepletion is a method to reduce contaminant leukocytes. Myeloperoxidase (MPO) is an enzyme produced by polymorphonuclear cells that have the potential to change structure and function of platelets when there is interaction between them during storage. The aim of this study is assessing the difference in myeloperoxidase level of TC based on its preparation method (leukodepleted and non-leukodepleted) and time storage. A cross-sectional observational study was conducted at the Blood Transfusion Services Unit, Dr. Sardjito hospital, Yogyakarta from April to December 2014. Thrombocyte Concentrate products was grouped based on storage time (â‰¤ and >72 hours) and preparation method (leukodepleted and non-leukodepleted), their MPO was then measured. Mean difference in each group was analyzed using ANOVA test and post hoc test with statistical significance level of p < 0.05. There were 64 eligible subjects, consisted of 29 leukodepleted TCs and 35 non-leukodepleted TCs, based on their storage time, 31 TCs had â‰¤72 hours storage time and the other 33 TCs > 72 hours. There were significantly lower median MPO level in â‰¤72 hours TCs than > 72 hours in non-leukodepleted TC group (13.23 ± 6.47 ng/mL vs 15.58 ± 7.82 ng/mL; p = 0.017). In TC group with more than 72 hours storage time, median MPO level in non-leukodepleted was significantly higher than leukodepleted TC (15.58 ± 7.82 ng/mL vs. 11.11 ± 3.97 ng/mL; p = 0,001). Myeloperoxidase level was lower in non-leukodepleted TC group with â‰¤ 72 hours than > 72 hours storage time. Furthermore, the MPO level was higher in leukodepleted TC than non-leukodepleted TC in > 72 hours storage time.